The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2133.2004.06186.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological effects of tazarotene 0.1% cream vs. vehicle on photodamaged skin: a 6-month, multicentre, double-blind, randomized, vehicle-controlled study in patients with photodamaged facial skin

Abstract: Treatment of photodamaged skin with tazarotene is associated with an amelioration of keratinocytic and melanocytic atypia, an improvement in epidermal polarity, and an increase in epidermal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Recent studies indicate that the skin flushing response is mediated by activation of receptors on epidermal Langerhans cells (50) or macrophages at concentrations above 0.1 mm (51). While prior studies have shown that the thickness of the stratum corneum is less in paraffin sections compared with frozen sections (52), paraffin sections have been used to assess stratum corneum morphology and changes in thickness in numerous studies (53)(54)(55)(56)(57). Using skin NAD as a biomarker of nicotinic acid delivery, MN was shown to deliver nicotinic acid to skin ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the skin flushing response is mediated by activation of receptors on epidermal Langerhans cells (50) or macrophages at concentrations above 0.1 mm (51). While prior studies have shown that the thickness of the stratum corneum is less in paraffin sections compared with frozen sections (52), paraffin sections have been used to assess stratum corneum morphology and changes in thickness in numerous studies (53)(54)(55)(56)(57). Using skin NAD as a biomarker of nicotinic acid delivery, MN was shown to deliver nicotinic acid to skin ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A shorter study of 6 months' duration of 0.1% tazarotene cream use in 50 patients also noted decreases in keratinocyte and melanocyte atypia at the end of the trial. 57 The above-mentioned studies raise the possibility that topical retinoids may have a place in the chemoprevention of skin cancers as well. Further clinical investigations are needed to reach a definitive conclusion.…”
Section: Vitamins As Therapymentioning
confidence: 97%
“…Machtinger and colleagues (2004) evaluated the histological effects of tazarotene cream in 50 patients with photodamaged facial skin by conducting a multicentre, double-blind, randomized, vehicle-controlled study. Blinded assessments showed that the tazarotene-treated group showed amelioration of keratinocytic and melanocytic atypia compared to the vehicle-treated group.…”
Section: Tazarotenementioning
confidence: 99%